2012
DOI: 10.1016/j.vaccine.2012.01.069
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric calicivirus-like particles elicit specific immune responses in pigs

Abstract: Virus-like particles (VLPs) have received considerable attention due to their potential application in veterinary vaccines and, in particular, VLPs from rabbit haemorrhagic disease virus (RHDV) have successfully shown to be good platforms for inducing immune responses against an inserted foreign epitope in mice. The aim of this study was to assess the immunogenicity of chimeric RHDV-VLPs as vaccine vectors in pigs. For this purpose, we have generated chimeric VLPs containing a well-known T epitope of 3A protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…In addition, we have shown that RHDV VLPs are good platforms for inducing immune responses against inserted heterologous cytotoxic CD8+ T-cell epitopes and CD4+ T-helper epitopes, in mice and pigs3940. Other studies have addressed the potential of RHDV VLPs as a platform for delivery of tumor-associated antigens, demonstrating their ability to elicit protective cellular immunity against tumors41.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, we have shown that RHDV VLPs are good platforms for inducing immune responses against inserted heterologous cytotoxic CD8+ T-cell epitopes and CD4+ T-helper epitopes, in mice and pigs3940. Other studies have addressed the potential of RHDV VLPs as a platform for delivery of tumor-associated antigens, demonstrating their ability to elicit protective cellular immunity against tumors41.…”
Section: Discussionmentioning
confidence: 94%
“…Recent investigations have also shown the significance of RHDV VLP obtained from cultured cells for the incorporation of foreign T-cells epitopes by genetic fusion or chemical conjugation and the generation of humoral and cell-mediated specific responses [31][34]. Therefore, an additional experiment was accomplished to investigate their feasibility as carriers of a B-cell epitope from Classical Swine Fever Virus (CSFV), an important disease in swine responsible for a highly contagious and fatal multisystemic disease that negatively impacts both animal health and economic issues worldwide [35], [36].…”
Section: Introductionmentioning
confidence: 99%
“…These features, which led to the description of VLPs as self-adjuvanting immunogen delivery systems (6,7), make VLPs attractive stand-alone vaccine candidates for many diseases (8)(9)(10)(11). In addition, VLPs can also be used as platforms for the multimeric display of foreign antigens (12)(13)(14)(15). Here we introduce a strategy for engineering chimeric VLPs for presentation of heterologous proteins to the immune system, using the capsid of the infectious bursal disease virus (IBDV).…”
mentioning
confidence: 99%